Seven in absentia homolog 1A mediates ubiquitination and degradation of group 1 metabotropic glutamate receptors - Moriyoshi, Koki (National Academy of Sciences, 2004)
Seven in absentia homolog 1A (Siah1A) is a member of the RING-finger-containing E3 ubiquitin ligases and has been shown to bind to the Siah-interacting domain (SID) at the carboxyl-terminal tails of the long splice forms of group 1 metabotropic glutamate receptors (mGluR1a and mGluR5). We examined the function of Siah1A in ubiquitination and degradation of group 1 mGluRs in heterologously expressing cell lines. Coexpression of Siah1A markedly decreased the SID-containing splice forms of group 1 mGluRs but not the SID-lacking mGluR1b splice form or the SID-deleted mGluR1a mutant. The decrease of mGluR1a resulted from accelerated protein turnover, as revealed by pulse–chase experiments. The Siah1A-mediated degradation of group 1 mGluRs was abrogated by not only mutations at the RING-finger domain of Siah1A but also treatment with a proteasome inhibitor. Siah1A coexpression induced strong ubiquitination of group 1 mGluRs. Replacements of lysine residues with arginine showed that Siah1A-mediated ubiquitination occurs at multiple lysine residues spanning both the seven-transmembrane region and carboxyl-terminal tail of mGluR5. In situ hybridization histochemistry showed a wide-spread distribution of Siah1 mRNAs, with high expression in the hippocampal pyramidal neurons and cerebellar Purkinje cells. Group 1 mGluRs play critical roles in the neural plasticity in both the hippocampal neurons and Purkinje cells. This investigation indicates that Siah1A serves as a selective ubiquitin ligase that mediates ubiquitination-dependent degradation of long splice variants of group 1 mGluRs and would contribute to posttranslational down-regulation of group 1 mGluRs.